Relationship between academic procrastination and self-efficacy amongst dental undergraduate students at a public university in Karachi, Pakistan - Shah, Hina; Ahmed, Sanaa; Raza, Syed Moosa; Irshad, Marium; Fahim, Hana; Usman, Taha (Journal of the Pakistan Medical Association, 2024)
Objectives: To compare the procrastination and self-efficacy scores among students with respect to the academic year of dental undergraduate programme, and to assess the relationship between self-efficacy and academic procrastination among the students. Method: The descriptive study was conducted at Sindh Institute of Oral Health Sciences, Jinnah Sindh Medical University, Karachi, from January to March 2023, and comprised medical students of either gender from all the 4 academic years. Data was collected using a structured questionnaire whose validity was assessed using a pilot study. Data was analysed using SPSS 18. Results: Of the 136 students, 84(61.8%) were females and 52(38.2%) were males. There were 34(25%) students from the 1st year, 32(23.5%) from 2nd year, 38(28%) from the 3rd year, and 32(23.5%) from the final year. The highest mean score for procrastination was from 3rd year students 67.7±12.8, while the highest mean score for self-efficacy was from 1st year students 30.2±4. There was no significant difference in terms of gender (p>0.05). Procrastination scores had a significant association with the academic year (p=0.016). Conclusion: Procrastination scores were high among the dental students with the highest score from 3rd year students. The academic environment should provide support help the students devise strategies to optimally utilise the available time. Key Words: Procrastination, Suicidal ideation, Workload, Motivation, Depression.